2005
DOI: 10.1579/0044-7447-34.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Deposition and the Biodiversity of Boreal Forests: Implications for the Nitrogen Critical Load

Abstract: The critical load concept is used to establish the deposition levels which ecosystems can tolerate without significant harmful effects. Here we summarize work within the Swedish research program Abatement Strategies for Transboundary Air Pollution (ASTA) assessing the critical load of N for boreal forests. Results from both field experiments in an area with low background N deposition in northern Sweden, and from a large-scale monitoring study, show that important vegetational changes start to take place when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
104
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(110 citation statements)
references
References 0 publications
2
104
2
2
Order By: Relevance
“…The ericaceous dwarf shrubs Ledum palustre and Vacciniumu liginosum formed the keystone species of the boreal forest understory vegetation (Nordin et al 2005). They usually occur on mesic sites that have less well drained soil with discontinuous permafrost, lower soil temperature, decomposition rates and nutrient availability.…”
Section: Relative Importance Of Factors On Sapling and Understory Vegmentioning
confidence: 99%
See 1 more Smart Citation
“…The ericaceous dwarf shrubs Ledum palustre and Vacciniumu liginosum formed the keystone species of the boreal forest understory vegetation (Nordin et al 2005). They usually occur on mesic sites that have less well drained soil with discontinuous permafrost, lower soil temperature, decomposition rates and nutrient availability.…”
Section: Relative Importance Of Factors On Sapling and Understory Vegmentioning
confidence: 99%
“…This may be because the main understory shrub species, Ledum palustre and Vacciniumu liginosum, have ericoid mycorrhiza which make them capable of acquiring organic N (Nordin et al 2005). They are well adapted to sites with acid and high moisture soils in the boreal region.…”
Section: Relative Importance Of Factors On Sapling and Understory Vegmentioning
confidence: 99%
“…However, there is evidence that species composition, diversity and ecosystem functions are affected at relatively low levels of N deposition (Bobbink et al 2010), although the effects of N deposition have been shown to be most pronounced where N is limiting (Bobbink et al 2003). Nordin et al (2005) concluded that while understorey vegetation reacts quickly to increasing N levels, recovery is a very slow process. In addition, we can anticipate that the recovery after reduced N deposition may be delayed since N deposition is still higher than pre-industrial levels.…”
Section: Introductionmentioning
confidence: 99%
“…Scandinavia) increasingly apply fertilizers to forests (Lindkvist et al 2011). These two types of anthropogenic N inputs can have numerous consequences in N-limited boreal forests, such as increase net primary productivity and aboveground carbon (C) stocks (De Vries et al 2006;Gundale et al 2014), alter species composition and community structure (Bobbink et al 1998 and references therein; Nordin et al 1998;Strengbom et al 2003;Nordin et al 2006), and reduce diversity (Nordin et al 2005;Bobbink et al 2010;Meunier et al 2016). While impacts of N enrichment on aboveground properties are well studied, relatively little is known about how soil processes respond to N enrichment (but see e.g.…”
mentioning
confidence: 99%